An examination of equal access in athletic programs throughout public high schools in the United States - Buchanan, Rebecca R.; Odenheimer, Eleanor F.; Prewitt-White, Tanya R. (Journal of Amateur Sport, 2016)
The mission of the U.S. Department of Education is “to promote student achievement and preparation for global competitiveness by fostering educational excellence and ensuring equal access” (www.ed.gov). As an extension of U.S. public education institutions, secondary afterschool programs involving physical activity are theoretically designed to enhance and support the educational mission of public schools. Yet, due to the hyper-commodification of youth sports, “equal access” in sport and physical activity is becoming increasingly limited to parameters grounded in highly competitive environments reflecting broader sport trends in society. An interesting paradox emerges in public school settings where the importance of physical activity for adolescents is also emphasized. However, in reality, the majority of public tax dollars funding extracurricular opportunities to be physically active are only for those who are highly competitive, physically literate and have the financial means to assist in the funding of their sport experiences. There are also issues related to gender in terms of who is being served. Therefore, it is importance to examine how public resources relating to physical activity and health are being unequally allocated in the public school setting.